2020
DOI: 10.14198/jhse.2022.173.14
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ACTN3 R577X and ACE I/D polymorphisms in young Colombian athletes: An exploratory research

Abstract: There are genetic sequences that might be associated with improved athletic performance, such as the α-actinin-3 (ACTN3) R577X polymorphism and the angiotensin-converting enzyme (ACE) insertion/deletion (I/D), which are related to phenotypes of increased muscle strength and endurance, respectively. This STREGA-based crosssectional study compared the genotype and allele frequencies of the ACTN3 R577X and ACE I/D polymorphisms between Colombian athletes (n = 37) and non-athletic controls (n = 37). Genotyping was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…α-Actinin-3 is encoded by the ACTN3 gene, and its expression in glycolytic skeletal muscle contributes to enhancing muscle function and coordinating fast-twitch muscles ( Yang et al, 2003 ). Ortiz et al (2022) reported that Colombian athletes carrying the RX genotype might express more ACTN3 protein that is involved in the optimization of muscle contraction in fast-twitch fiber. The frequency of the RR genotype was revealed to be higher in male skiers than in the control group, but male skiers with the XX genotype evidently had an increased VO 2 peak within 5 years ( Magi et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…α-Actinin-3 is encoded by the ACTN3 gene, and its expression in glycolytic skeletal muscle contributes to enhancing muscle function and coordinating fast-twitch muscles ( Yang et al, 2003 ). Ortiz et al (2022) reported that Colombian athletes carrying the RX genotype might express more ACTN3 protein that is involved in the optimization of muscle contraction in fast-twitch fiber. The frequency of the RR genotype was revealed to be higher in male skiers than in the control group, but male skiers with the XX genotype evidently had an increased VO 2 peak within 5 years ( Magi et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%